The Effect of Herbal Teas on Management of Polycystic Ovary Syndrome: A Systematic Review - Mitra Kolivand; Afsaneh Keramat; Ahmad Khosravi (Mashhad University of Medical Sciences, 2017)
Background & aim: Polycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder. Recently, the tendency towards complementary therapies such as using herbs with anti-androgenic effects has been increased. This study reviewed the documents related to the effect of four types of herbal teas on the treatment of PCOS based on the literature review. Methods: The searched databases included ISI, PubMed, Google Scholar, Scopus, Science Direct, Cochrane library, International Clinical Trials registry, MedLib, Society for Information Display (SID), Iranian Registry of Clinical Trials (IRCT), IranMedex and Magiran,. The databases were searched for the clinical trials without any time limit and using English and Persian key terms included "polycystic ovarian syndrome", "herbal therapy", and "herbal medicine". Results: Among 104 randomized controlled trials (RCTs) about the effects of herbal medicines on the treatment of PCOS, only four studies were conducted on diverse types of tea. The results of one study on the effects of mint tea revealed a significant reduction in the total and free testosterone levels in the intervention group (P0.05). Another clinical trial determined the same effects ofusing Stachys lavandulifolia and hormone therapy. Accordig to another study, the level of dehydroepiandrosterone-sulphate (DHEA-S) significantly dropped after treatment with marjoram tea (P=0.05). Conclusion: The positive effects of various types of herbal teas on PCOS has been reported in different trials; however, further RCTs are recommended with larger sample size and prolonged duration.